Impact of Electricity Supply, Inflation and Exchange Rate Shocks on Import Flows in South Africa - Habanabakize, Thomas; Zerihun, Mulatu Fekadu (Acta Universitatis Danubius. Œconomica, 2024)
Import flows are one of the major economic variables that play a significant role in global trade and determine a country’s economy’s performance. The current article imperially scrutinizes the symmetric relationship between energy electricity supply, inflation rate, exchange rate and import flows in South Africa. This objective was achieved through the application of econometric models such as ARDL, ECM and T-Y approaches. These approaches were applied on monthly time series from January 2002 to October 2022. The results indicated the presence of long-run and short-run import flows behaviour electricity supply, inflation and exchange rate volatility. While the inflation rate and electricity supply positively influence long-run import flows, the latter is negatively influenced by exchange rate volatility. To improve import flows in South Africa, the study recommends policymakers’ caution in selecting the country’s adequate exchange rate regime and considering electricity supply and inflation rate while establishing the country’s terms of trade.